Humic acid type amino-phosphoric acid functionalized hydrogel adsorption material as well as preparation method and application thereof
Through humic acid-type amino-phosphate functionalized hydrogel adsorption materials, using etherification modification and Schiff alkali structure and other technologies, the problem of insufficient structure of traditional adsorbent materials is solved, and efficient adsorption and recycling of heavy metals and organic matters is achieved. , provides an effective environmental governance plan.
Patent Information
- Application Number
- CN202411505960.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional adsorbent materials have shortcomings in their structure and characteristics, making it difficult to efficiently adsorb macromolecular pollutants, and their adsorption capacity decreases after recycling, making it impossible to effectively remove harmful substances.
Using humic acid-type amino-phosphate functionalized hydrogel adsorption materials, the adsorption capacity is enhanced by etherification modification of natural polysaccharides and phosphate ester group introduction, combined with Schiff alkali structure, montmorillonite and potassium humate, and enhanced adsorption capacity through Various interaction mechanisms achieve efficient adsorption.
It significantly improves the adsorption capacity of heavy metal ions and organic matter, has good circulation performance and high efficiency, is suitable for water and soil pollution treatment, and provides a new environmental governance solution.
Smart Images

Figure CN119258995A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, relates to a polymer gel adsorption material, and specifically relates to a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material and a preparation method and application thereof. Background Art
[0002] In recent years, various organic chemicals, synthetic dyes, heavy metals and other harmful substances have been discharged into rivers, lakes and groundwater at will, seriously damaging the ecological environment of water bodies. Therefore, in view of the current status of water pollution, effective purification measures must be taken to restore and protect the quality of water resources.
[0003] At present, the main method for treating water pollution and heavy metal pollution in soil is adsorption. Traditional adsorption materials have deficiencies in structure, characteristics and adsorption capacity, which are not conducive to the efficient adsorption of pollutants. It is manifested in: First, there are deficiencies in structure. The internal pore size and distribution of the adsorption material may not be ideal, resulting in limited specific surface area, making it difficult to adsorb large molecular pollutants. At the same time, its mechanical strength is low, and it is easy to deform or break under the action of external force, making it difficult to achieve the expected effect in practical applications. Second, the prepared adsorption materials often face the problem of insufficient binding groups, which greatly limits their ability and adsorption capacity for specific pollutants, resulting in the failure to effectively remove certain harmful substances. Secondly, in practical applications, adsorption materials usually need to be reused many times. After multiple cycles of use, some active sites may be permanently occupied or damaged, resulting in a reduction in the effective adsorption surface area and a gradual decrease in the adsorption capacity.
[0004] In view of the shortcomings of the above-mentioned adsorption materials, it is of great significance to develop a universal hydrogel adsorbent with strong adsorption capacity, rich active sites and excellent cycle performance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material with strong adsorption capacity, rich active sites and excellent circulation performance, and a preparation method and application thereof. The preparation method is simple, the cost is low, and it can be used on a large scale.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material comprises the following steps:
[0008] Step 1: Dissolve 20 to 30 parts of natural polysaccharide in 200 parts of isopropanol by mass, then add 40 to 60 parts of 30% sodium hydroxide solution by mass to react for 2 to 3 hours, then drop 20 to 30 parts of modifier into the solution, place in a 35 to 40°C water bath and stir for 4 to 6 hours, crystallize in anhydrous ethanol, repeat three times, wash and dry the crystals to obtain modified natural polysaccharide;
[0009] Step 2: Heat and melt 30 to 50 parts of urea by mass, add 5 to 8 parts of the modified natural polysaccharide prepared in step 1 and 20 to 30 parts of phosphorous acid, stir and react for 5 to 8 hours, pour it into 40 parts of 30% sodium hydroxide solution by mass, recrystallize in anhydrous ethanol, repeat three times, wash and dry the crystals, and obtain a phosphate-modified natural polysaccharide;
[0010] Step 3: Dissolve 4 to 8 parts of the phosphate-modified natural polysaccharide prepared in step 2 in 10 to 20 parts of acetic acid by mass, then add 3 to 5 parts of a porogen, 4 to 6 parts of potassium sulfonated humate, 1 to 3 parts of montmorillonite and 50 to 60 parts of water, and stir at 35 to 40°C to obtain a mixed solution. After stirring until the system is uniform, add 1 to 3 parts of a cross-linking agent, heat to 70 to 80°C, react for 1 to 2 hours, and then soak in 80 to 100 parts of an organic solvent for 0.5 to 1 hour to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0011] The present invention also has the following technical features:
[0012] Preferably, the natural polysaccharide includes any one of chitosan, chitosan oligosaccharide, chitin, glucosamine, glucosamine, cellulose, pectin, β-cyclodextrin, gelatin and agar.
[0013] Preferably, the modifier includes any one of chloroacetic acid, dichloroethylamine hydrochloride, and tetrachloroacetic acid.
[0014] Preferably, the porogen includes any one of polyethylene glycol 1500, polyethylene glycol 2000, wood ash, potassium carbonate and calcium carbonate.
[0015] Preferably, the cross-linking agent includes any one of glutaraldehyde, aromatic aldehyde, vanillic dialdehyde, and L-(+)-arabinose.
[0016] Preferably, the organic solvent includes any one of anhydrous ethanol, ether and ethyl acetate.
[0017] Preferably, the stirring rate in step 1 is 200-300 r / min;
[0018] The stirring rate described in step 2 is 300-500 r / min;
[0019] The stirring rate described in step 3 is 400r / min.
[0020] The present invention also protects a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material prepared by the method as described above and its application in water pollution and soil pollution treatment.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] The invention uses natural products as raw materials to prepare a hydrogel with a three-dimensional network structure; by etherifying and modifying natural polysaccharides, phosphate groups are introduced to enhance the adsorption capacity of heavy metal ions and organic molecules; by cross-linking the modified natural products with aldehyde cross-linking agents, a Schiff base structure is successfully introduced into the hydrogel structure; the Schiff base structure can significantly enhance the adsorption capacity of the hydrogel for heavy metal ions, so that it exhibits higher specificity and efficiency in the field of treating heavy metal pollution; at the same time, in order to further enhance the active binding sites of the three-dimensional network structure and the relationship between organic matter and heavy metal pollutants, the hydrogel can be further improved. The invention introduces montmorillonite and potassium humate through the conjugation, chelation and coordination between the two materials, thereby further improving the adsorption capacity of the adsorption material, making it show strong efficiency in treating various pollutant molecules; the invention combines the joint action of physical adsorption and chemical adsorption; through various interactions such as hydrogen bonds, van der Waals forces, ion exchange, electrostatic attraction and coordination bonds, the material can effectively adsorb organic matter and heavy metal ions; in particular, the phosphate chelate group can significantly improve the stability and adsorption effect of metal ions by forming a stable ring structure with the pollutants and forming a strong coordination bond with metal ions such as iron, copper and zinc;
[0023] The preparation method of the invention is simple, low in cost, has strong adsorption capacity, rich active sites, excellent circulation performance, can be used on a large scale, is suitable for adsorbing pollutants to solve water pollution and soil pollution problems, and provides a new solution for environmental governance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the chitosan modification reaction formula of Example 1;
[0025] Figure 2 is the reaction formula for the phosphate group in Example 1;
[0026] Figure 3 This is a diagram of the preparation mechanism of the humic acid-type amino-phosphoric acid functionalized natural product adsorption material of Example 1. DETAILED DESCRIPTION
[0027] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0028] Example 1
[0029] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps. The reaction mechanism is as follows: Figure 1-3 As shown:
[0030] Step 1: Dissolve 20 parts of chitosan in 200 parts of isopropanol according to the mass fraction, then add 40 parts of 30% sodium hydroxide solution to react for 2 hours, then drop 20 parts of chloroacetic acid into the solution, and stir in a 35°C water bath for 4 hours at a stirring rate of 300 r / min, precipitate and filter in anhydrous ethanol, wash with ethanol 3 times, and freeze-dry to obtain carboxymethyl chitosan;
[0031] Step 2: Heat 30 parts of urea to 140°C for melting according to the mass fraction, add 5 parts of carboxymethyl chitosan prepared in step 1 and 20 parts of phosphorous acid, stir and react for 5 hours at a stirring rate of 400 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol three times, and freeze-dry to obtain phosphate carboxymethyl chitosan;
[0032] Step 3: Dissolve 4 parts of the phosphate carboxymethyl chitosan prepared in step 2 in 10 parts of acetic acid according to the mass ratio, then add 3 parts of polyethylene glycol 1500, 4 parts of potassium sulfonated humate, 2 parts of montmorillonite and 50 parts of water and stir at 35°C to obtain a mixed solution. After stirring until the system is uniform, add 3 parts of glutaraldehyde at a stirring rate of 400r / min, heat to 75°C, react for 1h, and then soak in 80 parts of anhydrous ethanol for 0.5h to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0033] Example 2
[0034] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0035] Step 1, according to the mass fraction, 20 parts of chitosan oligosaccharide are dissolved in 200 parts of isopropanol, and then 45 parts of 30% sodium hydroxide solution are added to react for 2.5 hours, and then 25 parts of dichloroethylamine hydrochloride are dropped into the solution, and the solution is placed in a 35°C water bath and stirred for 4 hours at a stirring rate of 200r / min, precipitated and filtered in anhydrous ethanol, washed with ethanol 5 times, and dried to obtain carboxymethyl chitosan oligosaccharide;
[0036] Step 2: Heat 35 parts of urea to 140° C. to melt, add 6 parts of carboxymethyl chitosan oligosaccharide prepared in step 1 and 25 parts of phosphorous acid, stir and react for 5 hours at a stirring rate of 300 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol 5 times, and dry to obtain phosphate carboxymethyl chitosan oligosaccharide;
[0037] Step 3: Dissolve 5 parts of the phosphate carboxymethyl chitosan oligosaccharide prepared in step 2 in 15 parts of acetic acid according to the mass ratio, then add 4 parts of polyethylene glycol 1500, 5 parts of potassium sulfonated humate, 2 parts of montmorillonite and 55 parts of water and stir at 40°C to obtain a mixed solution. After stirring until the system is uniform, add 3 parts of L-(+)-arabinose at a stirring rate of 400r / min. Heat to 75°C and react for 1h, then soak in 85 parts of ethyl acetate for 0.5h to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0038] Example 3
[0039] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0040] Step 1, according to the mass fraction, 30 parts of chitosan are dissolved in 200 parts of isopropanol, and then 50 parts of 30% sodium hydroxide solution are added to react for 3 hours, and then 30 parts of tetrachloroacetic acid are dropped into the solution, and the solution is placed in a 35°C water bath and stirred for 4 hours at a stirring rate of 300r / min, precipitated and filtered in anhydrous ethanol, washed with ethanol 4 times, and dried to obtain carboxymethyl chitosan;
[0041] Step 2: Heat 40 parts of urea to 140° C. to melt, add 7 parts of carboxymethyl chitosan prepared in step 1 and 30 parts of phosphorous acid, stir and react for 5 hours at a stirring rate of 500 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol 4 times, and dry to obtain phosphate carboxymethyl chitosan;
[0042] Step 3: Dissolve 6 parts of the phosphate carboxymethyl chitosan prepared in step 2 in 20 parts of acetic acid according to the mass ratio, then add 5 parts of wood ash, 6 parts of potassium sulfonated humate, 3 parts of montmorillonite and 60 parts of water and stir at 35°C to obtain a mixed solution. After stirring until the system is uniform, add 3 parts of aromatic aldehyde at a stirring rate of 400r / min. Heat to 75°C and react for 1h, then soak in 90 parts of ethyl acetate for 0.5h to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0043] Example 4
[0044] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0045] Step 1: Dissolve 20 parts of glucosamine in 200 parts of isopropanol according to the mass fraction, then add 55 parts of 30% sodium hydroxide solution to react for 2 hours, then drop 20 parts of tetrachloroacetic acid into the solution, and stir in a 35°C water bath for 4 hours at a stirring rate of 300 r / min, precipitate and filter in anhydrous ethanol, wash with ethanol 3 times, and dry to obtain carboxymethyl glucosamine;
[0046] Step 2: Heat 45 parts of urea to 140° C. to melt, add 8 parts of carboxymethyl glucosamine prepared in step 1 and 20 parts of phosphorous acid, stir and react for 5 hours at a stirring rate of 500 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol three times, and dry to obtain phosphate carboxymethyl glucosamine;
[0047] Step 3: Dissolve 7 parts of phosphate carboxymethyl glucosamine prepared in step 2 in 10 parts of acetic acid according to the mass ratio, then add 3 parts of polyethylene glycol 1500, 4 parts of potassium sulfonated humate, 1 part of montmorillonite and 50 parts of water and stir at 40°C to obtain a mixed solution. After stirring until the system is uniform, add 2 parts of glutaraldehyde at a stirring rate of 400r / min. Heat to 75°C and react for 1h, then soak in 95 parts of anhydrous ethanol for 0.5h to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0048] Example 5
[0049] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0050] Step 1: Dissolve 25 parts of glucosamine in 200 parts of isopropanol according to the mass fraction, then add 60 parts of 30% sodium hydroxide solution to react for 2.5 hours, then drop 25 parts of chloroacetic acid into the solution, and stir in a 38°C water bath for 5 hours at a stirring rate of 200 r / min, precipitate in anhydrous ethanol, filter and wash with ethanol 3 times, and dry to obtain carboxymethyl glucosamine;
[0051] Step 2: Heat 50 parts of urea to 140°C for melting according to the mass fraction, add 6 parts of carboxymethyl glucosamine prepared in step 1 and 25 parts of phosphorous acid, stir and react for 5 hours at a stirring rate of 400 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol three times, and dry to obtain phosphate carboxymethyl glucosamine;
[0052] Step 3: Dissolve 8 parts of the phosphate carboxymethyl glucosamine prepared in step 2 in 15 parts of acetic acid according to the mass ratio, then add 4 parts of potassium carbonate, 5 parts of potassium sulfonated humate, 2 parts of montmorillonite and 55 parts of water and stir at 35°C to obtain a mixed solution. After stirring until the system is uniform, add 2 parts of vanillin at a stirring rate of 400 r / min. Heat to 75°C and react for 1 hour, then soak in 100 parts of ethyl acetate for 0.5 hour to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0053] Example 6
[0054] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0055] Step 1: Dissolve 30 parts of pectin in 200 parts of isopropanol according to the mass fraction, then add 50 parts of 30% sodium hydroxide solution by mass fraction to react for 3 hours, then drop 30 parts of chloroacetic acid into the solution, and place it in a 40°C water bath and stir for 6 hours at a stirring rate of 260r / min, precipitate and filter in anhydrous ethanol, wash with ethanol 5 times, and dry to obtain carboxymethyl pectin;
[0056] Step 2: Heat 40 parts of urea to 140° C. to melt, add 7 parts of carboxymethyl shell pectin prepared in step 1 and 30 parts of phosphorous acid, stir and react for 8 hours at a stirring rate of 500 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol 5 times, and dry to obtain phosphate carboxymethyl pectin;
[0057] Step 3: Dissolve 6 parts of the phosphate carboxymethyl pectin prepared in step 2 in 20 parts of acetic acid according to the mass ratio, then add 5 parts of calcium carbonate, 6 parts of potassium sulfonated humate, 3 parts of montmorillonite and 60 parts of water and stir at 40°C to obtain a mixed solution. After stirring until the system is uniform, add 3 parts of glutaraldehyde at a stirring rate of 400r / min, heat to 78°C, react for 1.5h, and then soak in 90 parts of ether for 0.6h to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0058] Example 7
[0059] This embodiment provides a method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, comprising the following steps:
[0060] Step 1: Dissolve 30 parts of agar in 200 parts of isopropanol according to the mass fraction, then add 50 parts of 30% sodium hydroxide solution by mass fraction to react for 3 hours, then drop 30 parts of dichloroethylamine hydrochloride into the solution, and place it in a 35°C water bath and stir for 4 hours at a stirring rate of 300r / min, precipitate and filter in anhydrous ethanol, wash with ethanol 3 times, and dry to obtain carboxymethyl agar;
[0061] Step 2: Heat 40 parts of urea to 140° C. to melt, add 7 parts of carboxymethyl agar prepared in step 1 and 30 parts of phosphorous acid, stir and react for 6 hours at a stirring rate of 500 r / min, pour it into 40 parts of 30% sodium hydroxide solution, recrystallize in anhydrous ethanol, repeat three times, wash with ethanol 5 times, and dry to obtain phosphate carboxymethyl agar;
[0062] Step 3: Dissolve 6 parts of phosphate carboxymethyl agar prepared in step 2 in 20 parts of acetic acid according to the mass ratio, then add 5 parts of polyethylene glycol 2000, 6 parts of potassium sulfonated humate, 3 parts of montmorillonite and 60 parts of water and stir at 38°C to obtain a mixed solution. After stirring until the system is uniform, add 1 part of vanillic dialdehyde at a stirring rate of 400 r / min, heat to 80°C and react for 2 hours, then soak in 90 parts of organic solvent for 1 hour to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
[0063] In order to characterize the adsorption performance of the humic acid type amino-phosphoric acid functionalized hydrogel adsorbent material, the adsorption effect of the hydrogel adsorbent material synthesized in the embodiment was tested. The adsorbed methylene blue, Cu 2+ The solution with an initial concentration of 200 mg / L and the solution with an initial benzene concentration of 100 mg / L were placed in a constant temperature oscillating box at 298K, 308K and 318K for 300-350 min, centrifuged and left to stand for 30 min, and the absorbance of the supernatant was measured at 662 nm, 300 nm and 291 nm using a visible spectrophotometer. The removal rate after adsorption was calculated using formula (1):
[0064]
[0065] In formula (1), C0 and C e They represent initial concentration and equilibrium concentration respectively, in mg / L; R is the removal rate at equilibrium.
[0066] The removal rate of each substance was calculated. Table 1 shows the removal rate of various pollutants by the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material. As shown in Table 1:
[0067] Table 1 Removal rates of various pollutants by humic acid-type amino-phosphoric acid functionalized hydrogel adsorbent materials
[0068]
[0069]
[0070] Through the analysis of the data in Table 1, the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material prepared by the present invention has a good adsorption effect on methylene blue, Cu and other pollutants in common sewage. 2+ The adsorption of benzene has a good adsorption removal rate. At the same time, the adsorption material synthesized from natural products has good cyclic adsorption performance, which solves the pollution problems of heavy metal ions, organic matter and dyes in water bodies, and realizes the concept of recyclable use and use as a universal material.
[0071] In order to test the recycling performance of the hydrogel adsorption material, the adsorption materials prepared in the above 7 embodiments were respectively subjected to the treatment of MB, Cu 2+ , benzene was subjected to five cycles of adsorption-desorption experiments, and the results are shown in Table 2.
[0072] Table 2 Removal rate of humic acid type amino-phosphoric acid functionalized hydrogel adsorbent material after 5 adsorption-desorption treatments
[0073]
[0074] From Table 2, it can be seen that the first removal rate of the hydrogel adsorbent material for methylene blue can reach 98.44%, and after 5 adsorption-desorption treatments, the removal rate is still at a relatively high level, up to 70.56%; the first removal rate of benzene is 63.48%, and after five cycles of adsorption-desorption experiments, there is still a relatively high removal rate. The removal rate of Cu(II) can reach 73.56% for the first time, and after 5 cycles, the removal rate can reach 42.95%, which proves that the adsorbent material prepared by the present invention can be used in a long-term and stable cycle.
[0075] The above content is a further detailed description of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these. The natural polysaccharides in the technical scheme can also be cellulose, β-cyclodextrin, gelatin, and they are not listed one by one again. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, they can also make some simple deductions or substitutions, which should be regarded as belonging to the scope of protection of the present invention determined by the submitted claims.
Claims
1. A method for preparing a humic acid type amino-phosphoric acid functionalized hydrogel adsorption material, characterized in that: The following steps are involved: Step 1: Dissolve 20 to 30 parts of natural polysaccharide in 200 parts of isopropanol by mass, then add 40 to 60 parts of 30% sodium hydroxide solution by mass to react for 2 to 3 hours, then drop 20 to 30 parts of modifier into the solution, place in a 35 to 40°C water bath and stir for 4 to 6 hours, crystallize in anhydrous ethanol, repeat three times, wash and dry the crystals to obtain modified natural polysaccharide; Step 2: Heat and melt 30 to 50 parts of urea by mass, add 5 to 8 parts of the modified natural polysaccharide prepared in step 1 and 20 to 30 parts of phosphorous acid, stir and react for 5 to 8 hours, pour it into 40 parts of 30% sodium hydroxide solution by mass, recrystallize in anhydrous ethanol, repeat three times, wash and dry the crystals, and obtain a phosphate-modified natural polysaccharide; Step 3: Dissolve 4 to 8 parts of the phosphate-modified natural polysaccharide prepared in step 2 in 10 to 20 parts of acetic acid by mass, then add 3 to 5 parts of a porogen, 4 to 6 parts of potassium sulfonated humate, 1 to 3 parts of montmorillonite and 50 to 60 parts of water, and stir at 35 to 40°C to obtain a mixed solution. After stirring until the system is uniform, add 1 to 3 parts of a cross-linking agent, heat to 70 to 80°C, react for 1 to 2 hours, and then soak in 80 to 100 parts of an organic solvent for 0.5 to 1 hour to obtain a humic acid-type amino-phosphoric acid functionalized hydrogel adsorption material.
2. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The natural polysaccharide includes any one of chitosan, chitosan oligosaccharide, chitin, glucosamine, glucosamine, cellulose, pectin, beta-cyclodextrin, gelatin and agar.
3. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The modifier includes any one of chloroacetic acid, dichloroethylamine hydrochloride and tetrachloroacetic acid.
4. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The porogen includes any one of polyethylene glycol 1500, polyethylene glycol 2000, plant ash, potassium carbonate and calcium carbonate.
5. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The cross-linking agent includes any one of glutaraldehyde, aromatic aldehyde, vanillic dialdehyde and L-(+)-arabinose.
6. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The organic solvent includes any one of anhydrous ethanol, ether and ethyl acetate.
7. The method for preparing the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material according to claim 1, characterized in that: The stirring rate described in step 1 is 200-300 r / min; The stirring rate described in step 2 is 300-500 r / min; The stirring rate described in step 3 is 400r / min.
8. A humic acid type amino-phosphoric acid functionalized hydrogel adsorption material prepared by the method according to any one of claims 1 to 7.
9. Use of the humic acid type amino-phosphoric acid functionalized hydrogel adsorption material as claimed in claim 8 in the treatment of water pollution and soil pollution.
Citation Information
Cited By
Ultra-high performance concrete as well as preparation method and application thereof
CN119528522A